Estrogen receptor-positive adenocarcinoma of the cervix presenting during pregnancy: Two case reports and review of the literature - James C.M. Wang; Laurence Bernard; Odette Boutross-Tadross; Sarab Mohamed; Sarah Alghamdi; Amir Salehi; Monalisa Sur; Lorraine Elit; Lua R. Eiriksson (Elsevier, 2022)
The incidence of adenocarcinoma of the cervix in pregnancy is exceptionally rare, and thus there is no consensus on its management. Here, we report two cases of adenocarcinoma of the cervix diagnosed in the context of pregnancy. In our first case, a patient referred to colposcopy for atypical glandular cells of undetermined significance was subsequently diagnosed with well differentiated endocervical adenocarcinoma on cone biopsy. Just prior to the cone biopsy, she was incidentally found to have a first trimester pregnancy loss. The patient subsequently underwent a radical hysterectomy and bilateral sentinel lymph node dissection. Final pathology revealed a stage 1B1 (FIGO 2009) well differentiated adenocarcinoma of the cervix. Interestingly, the tumour was positive for estrogen receptor, which is unusual for cervical adenocarcinoma.In our second case, a patient presented with a pedunculated, exophytic cervical neoplasm at 31 weeks GA with self-limiting antepartum hemorrhage. The primary lesion measured 52 mm in diameter on MRI and was amputated at the base during the patient's elective repeat cesarean section. Final pathology revealed a stage IB2 (FIGO 2009) mucinous adenocarcinoma of the cervix. The patient subsequently underwent a radical hysterectomy and bilateral pelvic lymph node dissection 17 weeks after initial presentation. The depth of invasion was 2.2 mm, restricted to the inner third of the cervical wall, and there was no lymphovascular space invasion in the surgical specimen. Surgical margins, parametria, and lymph nodes were all negative for adenocarcinoma. This tumour was also found to be estrogen receptor/progesterone receptor (ER/PR) positive, again unusual for cervical adenocarcinoma. P16 was strongly positive and HPV DNA studies were also positive for human papilloma virus 18. The patient received adjuvant external beam radiotherapy to the pelvis and currently remains in remission.